Situation Report: Czechoslovakia, 5 February 1968 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Dubcek Meets Kadar The Seventh Congress of Collective Farms Dubcek Outlines His Policy Smrkovsky on Necessary Changes Goldstuecker [Goldstücker] on Writers and Students Pre-war Party Members Write to Dubcek